Design of a MIMO Antenna with Improved Isolation Using MNG Metamaterial. (4th July 2012) - Lee, Youngki; Ga, Deukhyeon; Choi, Jaehoon
Abstract : A multi-input multi-output (MIMO) antenna with improved isolation using an interdigital split ring resonator (SRR) is proposed. The necessary impedance bandwidth is obtained by utilizing the coupling between the meander strip and an inverted L strip. Using interdigital SRR, a negative permeability was generated, while achieving improved isolation between the two radiating elements. The fabricated antenna satisfies the 10 dB return loss in the long-term evolution (LTE) band 40 from 2.3 GHz to 2.4 GHz. The measured peak gains of the two elements were 2.0 dBi and 1.3 dBi. The measured envelope correlation coefficient was less than 0.16 over the frequency band of interest.